Private equity and venture capital in sport: Who is receiving funding and what factors influence funding - Timothy Koba (The Journal of Entrepreneurial Finance (JEF), 2020)
Small business survival is paramount to the vibrant business community in the United States with over 400,000 new business created annually. While the cost of starting a business can vary, the necessity of access to available capital is vital for growth. As an industry, sport comprises several sectors of the economy with little understanding of the private equity market that exists for funding of these businesses. This paper investigates the 9.2 Billion private equity marketplace for sport, fitness and athletic businesses in the United States between 2010 and 2020. The results of the study demonstrate the importance of revenue and total investors to the ability to attract investment dollars, as well as the capital invested in women and minority sport business. As one of the first studies to evaluate this funding, results help inform academics and practitioners on this area.
Keywords: 650; sport; private equity; venture capital